PENGARUH WAKTU ETSA TERHADAP KEKUATAN GESER PADA PERLEKATAN ULANG BRAKET BEGG - , Robertus Meidiyanto, drg. Wayan Ardhana., M.S., Sp. Ort (K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Accidental dislodgement of an orthodontic bracket due to occlusal trauma or intentional removal of bracket in order to reposition it to achieved ideal occlusal goals was one of the problem orthodontist frequently found in treat orthodontic patients. The orthodontist would frequently face rebounded brakets. The aim of this study was to determine the influence of etching time on the shear strength of rebonding Begg bracket on incisors teeth. The study was using 15, 30, 60 seconds etching time. Material and Methods : Thirty incisors were used for sample size and then etched using 37% phosphoric acid for 15 seconds according to the manufacturer's instructions, bond with Begg bracket then debonded. Shear bond strengths were measured using Universal testing machine, and the residual adhesives were removed using tungsten carbide bur, continued with enhance and finish with soft rubber cup with pumice and water for 10 seconds. Teeth were randomly divided into three groups then rebonded with 15, 30, and 60 second etching time. The shear bond strengths were measured again using Universal testing machine. Research was analyzed using one-way Anova. The results showed that there was no significant difference in shear bond strength (p> 0.05) between initial etching time bond and the tested etching time of rebonding with 15, 30, 60 seconds. Prolong etching time did not effect the shear bond strength of rebounded bracket.